Effect of anti-tuberculosis therapy on polymorphic drug metabolizing enzyme CYP2C9 using phenytoin as a probe drug - George, Melvin (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Patients on anti-tuberculosis therapy (ATT) are more prone to drug interactions in the presence of coexisting illnesses which warrant drug therapy. Rifampicin is a strong CYP enzyme inducer while isoniazid is a potent CYP inhibitor. The objective of the study was to find the net effect of one month ATT on CYP2C9 enzyme and to correlate it with respect to the CYP2C9 genetic polymorphisms. MATERIALS AND METHODS: Forty eight newly diagnosed tuberculosis patients were included in the study based on the inclusion-exclusion criteria. Before commencing ATT, they were given a single dose of phenytoin 300 mg as a probe drug for CYP2C9. Blood sample was collected after three hours to carry out CYP2C9 genotyping by PCR-RFLP method. Phenotyping for CYP2C9 enzyme was done by measuring the ratio of phenytoin and its metabolite p-HPPH (para hydroxy phenyl hydantoin) by reverse phase HPLC (high performance liquid chromatography) method before and after one month of ATT. RESULTS: In the CYP2C9*1*1 genotype, the mean plasma concentrations of phenytoin before and after one month of ATT were 5.2 ± 0.3 μg/ml and 3.5 ± 0.4 μg/ml respectively, a reduction by 33% showing significant induction (P < 0.001). There was also significant decrease in the metabolic ratio after one month of ATT from 23.2 ± 4.8 to 10.1 ± 1.9 (P < 0.001). The metabolic ratio was also observed to reduce significantly (P < 0.05) when the CYP2C9*1*2, CYP2C9*1*3, and CYP2C9*3*3 data were pooled together. CONCLUSION: The presence of polymorphisms in the CYP2C9 gene does not affect the induction potential of ATT.